2015
DOI: 10.1007/s13277-015-3775-6
|View full text |Cite
|
Sign up to set email alerts
|

Fluorouracil induces autophagy-related gastric carcinoma cell death through Beclin-1 upregulation by miR-30 suppression

Abstract: The molecular mechanisms underlying the anti-cancer effects of chemotherapy drugs are not completely understood. Here, we studied the effects of fluorouracil (5-FU) on gastric carcinoma (GC) cells. We found that 5-FU dose-dependently inhibited the growth of GC cells, in either a cell counting kit-8 (CCK-8) assay or a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Moreover, autophagy-associated protein 6 (ATG6) or Beclin-1 was dose-dependently activated by 5-FU in GC cells. Further, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…Induction of autophagy can either be a pro-survival mechanism protecting cells against stress-induced killing [45,46] or a cell death mechanism induced by various anti-cancer agents [43,44,[47][48][49][50]. Our results showed that cells with initiation of autophagy were more resistant to Tenovin-6, although the autophagy flux was blocked (Figure 3), suggesting a protective role of autophagy in these cells.…”
Section: Discussionmentioning
confidence: 67%
“…Induction of autophagy can either be a pro-survival mechanism protecting cells against stress-induced killing [45,46] or a cell death mechanism induced by various anti-cancer agents [43,44,[47][48][49][50]. Our results showed that cells with initiation of autophagy were more resistant to Tenovin-6, although the autophagy flux was blocked (Figure 3), suggesting a protective role of autophagy in these cells.…”
Section: Discussionmentioning
confidence: 67%
“…Aberrant or excessive autophagic activity may produce cytotoxicity, resulting in autophagic cell death and suppressing tumor development in GC cells (Qian and Yang, 2016). Fluorouracil (5-FU) may induce cell proliferation arrest and autophagic cell death in GC cells by suppressing miR-30, resulting in upregulating Beclin1 (Yang and Pan, 2015). On the other hand, autophagy promotes tumor progression and prevents cancer cells from undergoing drug-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, high-level of autophagy was also demonstrated to suppress GC in other studies [9,12]. Some studies have given evidence that the upregulated autophagy can play a tumor suppressor role in GC cells [9,13]. For instance, Yang et al found that 5-Fu can suppress GC cells via inducing autophagy [13].…”
Section: Introductionmentioning
confidence: 94%
“…Some studies have given evidence that the upregulated autophagy can play a tumor suppressor role in GC cells [9,13]. For instance, Yang et al found that 5-Fu can suppress GC cells via inducing autophagy [13]. In addition, other pharmacological treatments can induce the autophagic cell death in GC cells [14,15].…”
Section: Introductionmentioning
confidence: 99%